A new species of the unusual leafhopper genus Phlogis Linnavuori (Hemiptera: Cicadellidae: Signoretiinae) from Uganda - Helden, Alvin J. (Zootaxa, 2022)
Phlogis kibalensis sp. nov. from Kibale National Park, Uganda is described and illustrated. It differs from the other species of the genus known from Africa (P. mirabilis) in the shape of the aedeagus, in particular the shape of the sub-apical lateral processes, as well as in style shape and some aspects of colouration.